Photodynamic inactivation of foodborne and food spoilage bacteria by curcumin - Penha, Camila Benedetti (2016)
Photodynamic inactivation (PDI) is a new and promising strategy to eradicate microorganisms such as Gram positive and Gram negative bacteria, yeasts, molds, viruses and parasites. This technique is based on the use of photosensitizer s (PSs) activated by an appropriate wavelength light. Among naturally occurring PSs, curcumin is a yellow pigment isolated from Curcuma longa and has been used as a spice since ancient times. Among its many biological activities are its antioxidant, antimicrobial, anti-HIV, anti-inflammatory and anticancer properties. The use of curcumin-mediated photosensitization has been reported against a range of bacteria and fungi. Evaluate antimicrobial photodynamic activity in vitro against pathogenic and spoilage bacteria using curcumin as a photosensitizer. Curcumin at 75 μM was used as a photosensitizer in the photodynamic inactivation experiments. The light source used was blue LED (λmax = 470 nm) and the light doses were calculated for the periods of 10 and 20 minutes of illumination. Standardized bacterial suspensions of Gram-positive bacterium Staphylococcus aureus ATCC 25923 and the Gram-negative bacteria Aeromonas hydrophila ATCC 7966; Escherichia coli ATCC 25922; Salmonella enterica serotype Typhimurium ATCC 14028 and Pseudomonas aeruginosa ATCC 27853 were made in 0.85% sterile saline using a McFarland Scale 0.5 and diluted to approximately 107 CFU/ml for use in the experiments. Aliquots of 50 μl of standardized bacterial suspension were incubated with 950 μl of curcumin solution at 75 μM in the dark for 10min. After incubation, 500 μl of the sample was illuminated with a blue LED. Two light exposure periods, 10 and 20 minutes, were evaluated, and the control was evaluated without light exposure. Afterwards serial dilutions of the treated and control samples were inoculated in trypticase soy agar (TSA; Difco) plates and incubated at 37°C/24h. The counting of colonies was carried out and the results of cell viability were expressed as log CFU/ml. The morphological changes of S. aureus and A. hydrophila induced by PDI with curcumin at 75 μM and irradiation by blue LED light for 10 minutes were examined by scanning electron microscopy. Cytotoxicity of PDI mediatedcurcumin was evaluated using VERO cells, in similar conditions to bacterial photoinactivation. Light doses obtained were 139 J/cm² for 10 minutes of illumination and 278J/cm² for 20 minutes. Curcumin at 75 μM in the absence of light activation did not reduce bacterial counts and the exposure of the bacteria to blue led light had no effect on its viability. PDI mediated by curcumin at 75 μM in S. aureus revealed significant differences in cell viability compared with the control group (p < 0.05). Exposure to LED blue light for 10 minutes displayed a reduction of approximately 3.27 log CFU/ml while after 20 minutes a reduction of approximately 3.57 log CFU/ml was observed. Among evaluated Gram negative bacteria, A. hydrophila displayed more sensibility to the treatment. A significant decrease (p < 0.05) in counts of 3.33log CFU/ml was observed after 10 minutes (139 J/cm2) of exposure. Additionally, complete photoinactivation was obtained after 20 minutes (278 J/cm2) of exposure to light. Reductions of 1.29 (p > 0.05) and 2.65 (p < 0.05) log CFU/ml were obtained for E. coli in light doses of 139 and 278 J/cm2, respectively and for S. Typhimurium the reductions were approximately 1.26 and 1.81 log CFU/ml (p>0.05), for 10 and 20 minutes of exposure to blue LED light, respectively. The treatment against P. aeruginosa exerted limited antimicrobial effects, resulting in only 0.24 and 0.3 log CFU/ml reductions with 10 and 20 minutes of exposure, respectively. Gram negative bacteria are significantly more resistant to PDI than Gram positive species, since present a complex outer membrane that work as a physical and functional barrier between the cells and the environment, while most Gram positive bacteria cells have a cell wall with a relatively high degree of porosity and permeability. The presence of S-layer in A. hydrophila could explain the sensibility and the best results to PDI by curcumin. The morphological changes of S. aureus induced by curcumin-mediated PDI showed a smooth cell surface when S. aureus was incubated with curcumin in the dark without LED exposure and with curcumin LED-irradiated for 10 minutes the cell membrane presented distortions and seemed shriveled and wrinkled. The morphological changes of the A. hydrophila induced by curcumin-mediated PDI showed the cell membrane with distortions and protrusion of small bubbles for the treatment at irradiation time of 10min while the control showed a smooth cell surface. The cytotoxicity of PDI mediated-curcumin in VERO cells showed a percentage of cell destruction of 13±0.05%, for both illumination times (10 and 20 minutes). Cytotoxicity assays are important for investigating the potential toxic effects of photodynamic therapy on the host cells and to avoid damage to basic cellular functions. An ideal PS should present no toxicity for the host cells and possess biological antimicrobial activity. The PDI by curcumin was effective in reducing bacterial counts. A. hydrophila and S. aureus were the most susceptible and P. aeruginosa was the most resistant to PDI. Photodynamic inactivation could serve as a new and promising approach to controlling foodborne and food spoilage bacteria.